Glioblastoma in the Cerebellopontine Angle in a Patient with Neurofibromatosis Type I: A Case Report and Review of the Literature - Shukairy, Mohammad Kareem; Ziegler, Andrea M.; Anderson, Douglas E.; Leonetti, John P. (Annals of Otology and Neurotology, 2019)
Introduction Glioblastoma multiforme (GBM) is the most common primary brain malignancy in adults and is typically in the supratentorial cerebral hemispheres. It has been reported to occur in the posterior fossa at the cerebellopontine angle (CPA), but the incidence is extremely rare.Case Report We report a case of a patient with a history of neurofibromatosis type I (NFI) diagnosed with a GBM arising in the CPA after presenting with facial numbness and pain. Patients with NFI are known to have an increased risk of developing both benign and malignant tumors, including a propensity for brainstem gliomas. However, there is no known association between NFI and tumors of the CPA. We believe this is the first reported case of a GBM of the CPA in a patient with NFI.Conclusion Although rare, GBM should be included in the differential diagnosis of a patient with a CPA tumor, especially in patients with increased risk of malignant pathology.
Keywords: cerebellopontine angle; neurofibromatosis type I; glioblastoma multiforme